From Administrative to Reflective Pedagogy: ISMUBA Teachers' Strategies for Internalizing Values in the Digital Era - Mardhatillah L. Rauf; Abd. Madjid (Journal of Educational Sciences, 2026)
ISMUBA (Al-Islam, Muhammadiyah, and Arabic) learning is the main identity of Muhammadiyah education which is directed at forming Islamic character and noble character of students. However, in practice, the effectiveness of learning strategies in internalizing Islamic values remains a challenge in the era of digital disruption. This study aims to analyze ISMUBA teachers' learning strategies in internalizing the values of faith and morals in Muhammadiyah elementary school students using a qualitative case study approach. Data were collected through in-depth interviews with three ISMUBA teachers and analyzed using thematic analysis techniques. The results of the study revealed five main findings: (1) Reflective contextual learning planning; (2) Differentiation of strategies based on the characteristics of Generation Z students; (3) Three models of Muhammadiyah value integration (personal contextual, fundamental applicative, normative referential); (4) Adaptive responses to contemporary learning challenges; (5) Holistic evaluation efforts amidst systemic limitations. This study concludes that although teachers have developed innovative strategies, it is necessary to strengthen the institutional support system and develop evaluation instruments capable of measuring value internalization comprehensively.